1991
DOI: 10.1346/ccmn.1991.0390406
|View full text |Cite
|
Sign up to set email alerts
|

Flocculation of Illite/Kaolinite and Illite/Montmorillonite Mixtures as Affected by Sodium Adsorption Ratio and pH

Abstract: Abstract--The effect of electrolyte concentration, exchangeable sodium percentage (ESP), sodium adsorption ratio (SAR), and pH on the flocculation-dispersion behavior of 50/50 mixtures of reference illite with reference kaolinite or reference montmorillonite was investigated. The clays were Na-or Ca-saturated and freeze-dried before use. Critical coagulation concentrations (CCCs) were investigated in the range of pH 5.9 to 9.6, percent Na-clay 0, 10, 20, 40, 60, 80, and 100 and SAR 0, 10, 20, 40, 60, 80, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Critical coagulation concentrations reported in the literature are difficult to compare with our measurements, because most investigators used much higher colloid concentrations. Corroborating our observation of a lower CCC at higher colloid concentration, reported kaolinite CCCs for Na (at pH 9 to 10 and 10 000 mg/L colloid concentrations) are between 10 and 40 mmol c/L (8), as compared to >100 mmolc/L in our experiments.…”
Section: Resultssupporting
confidence: 90%
“…Critical coagulation concentrations reported in the literature are difficult to compare with our measurements, because most investigators used much higher colloid concentrations. Corroborating our observation of a lower CCC at higher colloid concentration, reported kaolinite CCCs for Na (at pH 9 to 10 and 10 000 mg/L colloid concentrations) are between 10 and 40 mmol c/L (8), as compared to >100 mmolc/L in our experiments.…”
Section: Resultssupporting
confidence: 90%
“…The value of pzc for montmorillonite was about 2.5 (Hengpraprom et al, 2006). Most importantly, the pH-dependent charge makes a small contribution to the total CEC of montmorillonite in comparison with kaolinite (Goldberg et al, 1991). Thus, the CIP desorption as solution pH deceased from 8 to 2.5 was much less affected in comparison with kaolinite.…”
Section: Ph Effect On Cip Desorptionmentioning
confidence: 93%
“…For example, a classic study on Berea sandstone, which is commonly used in laboratory studies to represent petroleum reservoirs, demonstrated that colloid dispersion could be prevented at sufficiently low pH (Kia et al, 1987). This observation can be explained by Goldberg et al (1991). See Section 4.4 for explanation of points 5 and 6.…”
Section: Reservoir Damagementioning
confidence: 99%
“…The two simplifications are as follows: First, Fig. 8 plots CCC relationships at pH = 6.5, the lowest pH for which Quirk‐Schofield diagrams could be constructed using the data in Goldberg et al (1991). The magnitude of each CCC relationship at the reported pH of 5.0–6.0 would be smaller.…”
Section: Applications With Constant Phmentioning
confidence: 99%
See 1 more Smart Citation